Emerging Molecular Prospective of SARS-CoV-2: Feasible Nanotechnology Based Detection and Inhibition - Patra, Sushmita; Kerry, Rout George; Maurya, Ganesh Kumar; Panigrahi, Bijayananda; Kumari, Swati; Rout, Jyoti Ranjan (Frontiers in Microbiology, 2020)
The rapid dissemination of SARS-CoV-2 stipulates its vulnerability towards the communities and has attained the status of global pandemic. According to the estimation of worldometer, the SARS-CoV-2 affected cases and deaths are exponentially increasing worldwide, marking the mortality rate ~3.8 % with no probability of its cessation till now. Despite massive attempts and races among scientific communities in search of proper therapeutic options, the termination of this breakneck outbreak of COVID-19 has still not been made possible. Therefore, this review highlights the diverse molecular events induced by a viral infection such as autophagy, unfolded protein response (UPR) and inflammasome illustrating the intracellular cascades regulating viral replication inside the host cell. The SARS-CoV-2 mediated endoplasmic reticulum stress and apoptosis are also emphasized in the review. Additionally, host’s immune response associated with SARS-CoV-2 infection as well as the genetic and epigenetic changes have been demonstrated, which altogether impart a better understanding of its epidemiology. Considering the drawbacks of available diagnostics and medications, herein we have presented the most sensitive nano-based biosensors for the rapid detection of viral components. Moreover, conceptualizing the viral-induced molecular changes inside its target cells, nano-based antiviral systems have also been proposed in this review.